2016
DOI: 10.1007/s10458-016-9327-7
|View full text |Cite
|
Sign up to set email alerts
|

Requirements specification via activity diagrams for agent-based systems

Abstract: Goal-oriented agent systems are increasingly popular for developing complex applications that operate in highly dynamic environments. As with any software these systems have to be designed starting with the specification of system requirements. In this paper, we extend a popular agent design methodology, Prometheus, and improve the understandability and maintainability of requirements by automatically generating UML activity diagrams from existing requirements models; namely scenarios and goal hierarchies. Thi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 40 publications
0
2
0
Order By: Relevance
“…We have found that some researchers have extended a well-known methodology based on some necessities or on problems identification within the formal definitions. On the one hand, Prometheus was extended to improve the requirements understandability, and maintainability through the automatic generation of activity diagrams [25]. On the other hand, Gaia is extended in [26] to make it more practically applicable as model-driven engineering, and extended in [27] with the security model.…”
Section: Rq4: What Are the Most Applied Methodologies Framework Andmentioning
confidence: 99%
“…We have found that some researchers have extended a well-known methodology based on some necessities or on problems identification within the formal definitions. On the one hand, Prometheus was extended to improve the requirements understandability, and maintainability through the automatic generation of activity diagrams [25]. On the other hand, Gaia is extended in [26] to make it more practically applicable as model-driven engineering, and extended in [27] with the security model.…”
Section: Rq4: What Are the Most Applied Methodologies Framework Andmentioning
confidence: 99%
“…Misinterpretation between DM and optimization model in a SO approach can be disastrous, then, as it can result in the wrong problem being solved. As such, a valid translation from problem description to formal model is crucial [1]. This translation is non-trivial.…”
Section: Introductionmentioning
confidence: 99%